The Values of Tolerance in the Hadith and Their Relevance to National Life - Masruatus Saadah (CV Edujavare Publishing, 2026)
Tolerance is one of the fundamental values in Islam that plays an important role in maintaining social harmony, peaceful coexistence, and unity within pluralistic societies. The teachings of the Prophet Muhammad as recorded in the Hadith contain numerous examples and principles emphasizing compassion, justice, respect for diversity, and peaceful interaction among individuals regardless of religious, ethnic, or cultural differences. This study aims to examine the values of tolerance in the Hadith and analyze their relevance to national life in contemporary society. The research employs a qualitative descriptive approach through literature review and contextual analysis of Hadith literature, Islamic teachings on tolerance, and contemporary social conditions. The findings indicate that the Hadith strongly promotes values such as mutual respect, social justice, peaceful dialogue, moderation, and protection of human dignity. These teachings remain highly relevant for strengthening national unity, preventing social conflict, and promoting harmonious coexistence in multicultural societies. The study also reveals that tolerance in Islam does not imply weakening religious identity but rather encourages balanced attitudes based on wisdom, humanity, and ethical interaction. In modern national life characterized by diversity and globalization, the implementation of tolerance values derived from the Hadith can contribute significantly to social stability, democratic culture, and peaceful intercommunal relations. Therefore, strengthening understanding of tolerant Islamic teachings is essential for fostering inclusive citizenship and maintaining national integrity in contemporary society.